The Influence Non-Cash Payment Transactions on Inflation in Indonesia in the 2020-2024 Period - Permatahati, Hanifa Aulia; Fitanto, Bahtiar (Contemporary Studies in Economic, Finance and Banking, 2026)
The transformation of digital payment systems in Indonesia has driven a massive increase in cashless transactions, which has the potential to affect money circulation, aggregate demand, and ultimately price stability. This study aims to analyze the effect of debit cards, credit cards, electronic money, and QRIS on inflation in Indonesia using monthly data from 2020 to 2024. The method used is Autoregressive Distributed Lag (ARDL) to examine the dynamics of short-term and long-term relationships between variables. The results show that debit cards have a significant positive effect on inflation in the short and long term. Credit cards have a significant positive effect in the short term and a significant negative effect in the long term. Electronic money has a significant negative effect in the short term and no significant effect in the long term. QRIS has a significant positive effect in the short term and no significant effect in the long term. These findings indicate that not all non-cash payment instruments have the same impact on inflation, so the development of digital payment systems needs to be balanced with policies that maintain supply-side equilibrium.